The Effect of Transformational Leadership and Discipline Through Motivation on Employee Performance at The Telanaipura District Office, Jambi City - Wahyuni, Sri; Yamali, Fakhrul Rozi; Hapsara, Osrita (Dinasti Publisher, 2025)
1) The impact of discipline and transformational leadership on employee motivation is the first goal of this study. 2) How performance of employees is affected by discipline and transformational leadership. 3) How performance of employees is affected by motivation. 4) how performance of employees is affected by transformational leadership and discipline via motivation. In Jambi City, this study was carried out in the Telanaipura District Office. 71 employees made up the sample size. Saturated sampling is the term for this kind of sampling. Data analysis using Partial Least Squares (PLS) with a descriptive and verification technique. Transformational leadership is classified as good, according to the descriptive analysis's findings. Performance of employees, motivation, and discipline are all rated as high. The verification analysis's findings show that employee motivation and performance are significantly impacted by transformational leadership and discipline. Motivation has also been shown to modulate the effects of discipline and transformative leadership on performance of employees, indicating that motivation may have a positive and substantial impact on performance of employees.